Chin Augmentation Using Silastic Implants - Newberry, Christopher Ian; Mobley, Steven R. (Facial Plastic Surgery, 2019)
An aesthetically pleasing face is centered on strength, symmetry, and balance. A defined, well-projected chin and jawline are crucial to this harmony and recontouring the lower third of the face plays a significant role in plastic surgery. Chin augmentation can be performed with injectables, implantation, or osseous genioplasty. The selection of the best procedure is based on the type and extent of deformity. This article reviews chin augmentation with emphasis on alloplast implantation. The relevant anatomy, patient evaluation, implant indications and limitations, alloplast selection, and surgical techniques in implantation are presented.
Keywords: chin augmentation; chin implants; microgenia; alloplastic chin augmentation; genioplasty